Pannexin-1 Channels Are Essential for Mast Cell Degranulation Triggered During Type I Hypersensitivity Reactions - Harcha, Paloma A.; López, Ximena; Sáez, Pablo J.; Fernández, Paola; Barría, Iván; Martínez, Agustín D.; Sáez, Juan C. (Frontiers in Immunology, 2019)
Mast cells (MCs) release pro-inflammatory mediators through a process called degranulation response. The latter may be induced by several conditions, including antigen recognition through immunoglobulin E (IgE) or “cross-linking”, classically associated with Type I hypersensitivity reactions. Early in this reaction, Ca2+ influx and subsequent increase of intracellular free Ca2+ concentration are essential for MC degranulation. Several membrane channels that mediate Ca2+ influx have been proposed, but their role remain elusive. Here, we evaluated the possible contribution of pannexin-1 channels (Panx1 Chs), well-known as ATP releasing channels, in the increase of intracellular Ca2+ triggered during cross-linking reaction of MCs. The contribution of Panx1 Chs in the degranulation response was evaluated in MCs from wild type (WT) and Panx1 knock out (Panx1-/-) mice after anti-ovalbumin (OVA) IgE sensitization. Notably, the degranulation response (toluidine blue and histamine release) was absent in Panx1-/- MCs. Moreover, WT MCs showed a rapid and transient increase in Ca2+ signal followed by a sustained increase after antigen stimulation. However, the sustained increase in Ca2+ signal triggered by OVA was absent in Panx1-/- MCs. Furthermore, OVA stimulation increased the membrane permeability assessed by dye uptake, a prevented response by Panx1 Ch but not by connexin hemichannel blockers and without effect on Panx1-/- MCs. Interestingly, the increase in membrane permeability of WT MCs was also prevented by suramin, a P2 purinergic inhibitor, suggesting that Panx1 Chs act as ATP releasing channels impermeable to Ca2+. Accordingly, stimulation with exogenous ATP restored the degranulation response and sustained increase in Ca2+ signal of OVA stimulated Panx1-/- MCs. Moreover, opening of Panx1 Chs in Panx1 transfected HeLa cells increased dye uptake and ATP release but did not promote Ca2+ influx, confirming that Panx1 Chs permeable to ATP are not permeable to Ca2+. These data strongly suggest that during antigen recognition, Panx1 Chs contribute to the sustained Ca2+ signal increase via release of ATP that activates P2 receptors, playing a critical role in the sequential events that leads to degranulation response during Type I hypersensitivity reactions.